The authoritarian international tracing how authoritarian regimes learn in the post-Soviet space - Hall, Stephen G. 1953- (Cambridge University Press, 2023)
"Focusing on Russia and Eastern Europe, Hall argues that democracies can preserve their norms and values by better understanding how authoritarian regimes learn. It will be of interest to scholars, advanced students, and policymakers concerned with the politics of authoritarianism, and the politics of Russia, and Central and Eastern Europe"--
Keywords: Autoritärer Staat; Osteuropa; Europe, Eastern / Politics and government / 1989-; Russia (Federation) / Politics and government / 1991-; Former communist countries / Politics and government; Authoritarianism / Europe, Eastern; Authoritarianism / Russia (Federation); Europe de l'Est / Politique et gouvernement / 1989-; Autoritarisme / Europe de l'Est; Autoritarisme / Russie; Authoritarianism; Politics and government; Eastern Europe; Former communist countries; Russia (Federation); Since 1989